Calculation of Solid Waste Collection Induced Air Pollutant Emissions through Spatial Analysis for Different Vehicle Capacities: A Case Study in Cigli, Izmir - Sedat Yalçınkaya (Doğal Afetler ve Çevre Dergisi)
In this study, A Geographic Information System (GIS) based methodology was presented to calculate the emissions of solid waste collection induced important air pollutants (CO, NMVOC, NOx, PM, N2O, NH3, SO2 and CO2) and to analyze the effect of collection vehicle capacity (8 + 1 m3 and 13 + 1.5 m3) on pollutant emissions and the methodology was applied to the district of Cigli in Izmir. Determination of optimum routes, total distances and total vehicle driving times were calculated through GIS-based Vehicle Routing Problem (VRP) method. Afterwards, emissions were calculated through the multiplication of fuel consumptions, obtained as a result of GIS analysis, and emission factors related to vehicle and fuel type. Results show that total fuel consumption increases while the number of employees and vehicles required are reduced when large vehicles are used. Collection with the large vehicle resulted in 17% increase in all emissions compared to the small vehicle. This study provides solid waste management planners, with basic GIS knowledge, a simple and fast modeling method that can be applied with little data for planning optimal collection routes and calculating emissions.